CHARACTERIZATION OF THE MIDDLE YCHSMA PERIOD CERAMICS IN SITE OF ARMATAMBO, CENTRAL COAST OF PERU - Falconí, Iván (2008)
This work deals with the ceramic style Ychsma as soon as it talks about the Middle Ychsma phase, as it defines the Archaeological Project Armatambo. The investigations on this ceramic style have been concentrated in defining the ceramic sequence, without giving further attention to clarify the specific characteristics of each one of their phases. This is an attempt to detail the Middle Ychsma Phase, concentrating in morphologic, decorative and productive aspects that allow to recognize better their characteristics.